2021
DOI: 10.21608/ejchem.2021.64042.3377
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking , Synthesis and ADME Studies of New Pyrazoline Derivatives as Potential Anticancer Agents.

Abstract: Cancer is a significant worldwide public health issue. The adverse effects of anticancer chemotherapies still compromise the quality of life of patients. To identify new potential targeted anticancer agents, a series of pyrazoline derivatives were synthesized and evaluated for anticancer effects on A549 (human lung adenocarcenoma cell line). In silico evaluation methods were done before synthesis through molecular docking via genetic optimization for ligand docking (GOLD) Suite software with EGFR tyrosine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Topological polar surface area (TPSA) was calculated since it is crucial in determining medication bioavailability. (22) . All synthesized compounds' results showed that TPSA is below 140.…”
Section: Results Interpretation For Admementioning
confidence: 99%
“…Topological polar surface area (TPSA) was calculated since it is crucial in determining medication bioavailability. (22) . All synthesized compounds' results showed that TPSA is below 140.…”
Section: Results Interpretation For Admementioning
confidence: 99%
“…Compounds that are passively absorbed and have a TPSA <140 Ao are consequently assumed to have a high bioavailability; otherwise, this number denotes a low bioavailability of the molecule. [ 14 ] The ADME prediction results revealed that all compounds with TPSA <140 Ao are within the range of acceptable values. Each compound had a bioavailability of 0.55, indicating that it entered the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
“…Other challenges include resistance to chemotherapeutic drugs, a lack of selectivity, and substantial side effects in cancer treatment. As a result, novel and safest anticancer drugs with a larger range of cytotoxicity to cancer cells are required (Wabdan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%